The role of institutional and stakeholder networks in shaping social enterprise ecosystems in Europe. Issue 3 (7th November 2016) - Hazenberg, Richard; Bajwa-Patel, Meanu; Mazzei, Micaela; Roy, Michael James; Baglioni, Simone
Abstract : Purpose: This paper draws upon prior research that built a theoretical framework for the emergence of social enterprise ecosystems based upon the biological evolutionary theory. This paper aims to extend this previous research by practically applying the said theory to the development of stakeholder and institutional networks across Europe. Design/methodology/approach: Data from in-depth semi-structured interviews and focus groups were analysed using Constant Comparison Method. Data were generated from discussions with 258 key stakeholders in ten countries across Europe, exploring the historical, political, social, legal and economic factors that influence the patterns of a social enterprise seen in each country. Findings: The results identify the emergence of four social enterprise ecosystem types (Statist-macro, Statist-micro, Private-macro and Private-micro). These are used to explain the differences found in each of the ten country's social enterprise ecosystems. The results are discussed in relation to the evolutionary theory in social entrepreneurship and how "genetic" and "epigenetic" factors lead to the divergence of social enterprise ecosystems, and the impact that this has on the stakeholders and institutions that are present within them. Originality/value: A typology of ecosystems is presented, which can be used by policymakers across Europe to understand how best to support their local social economies.